Practical tuning guide to mixed feedback and feedforward control of soft-mounted vibration isolators. Issue 21 (2016) - Beijen, M.A.; Heertjes, M.F.; Butler, H.; Steinbuch, M.
Abstract: This paper proposes a practical tuning guide for mixed feedback and feedforward control design of active soft-mounted vibration isolators. A model is derived based on measured frequency response function data obtained from an industrial vibration isolator. Using this model, feedback and feedforward controllers are designed and evaluated. The mixed-sensor feedback controller uses a combination of relative position feedback and absolute acceleration feedback. By mixing the sensor signals, amplification of sensor noise is minimized. It is shown that feedback control can greatly enhance the disturbance rejection properties of disturbances that act directly on the payload of the machine. In addition, a feedforward controller is designed that improves the rejection of indirect disturbances on the machine, i.e. disturbances that are transmitted via the vibration isolator.